Iatrogenic Proximal Urethro–Rectal Perforation During Foley Catheter Insertion - Claude Tayar; Ali Alameh; Rawan Abdallah; Jamil Boufarah; Yehya Tlaiss; Hadi Farhat (Case Reports in Surgery)
Iatrogenic urethral–rectal perforation represents a rare but severe complication arising from medical interventions, notably highlighted in the context of Foley catheter insertion. This case report outlines the presentation, diagnosis, management, and outcomes of a 71-year-old male patient who experienced iatrogenic rectal perforation during the routine insertion of a Foley catheter, against the backdrop of several predisposing factors, such as atrial fibrillation, valvular disease, benign prostatic hyperplasia, urethral stenosis, and colorectal cancer with liver metastasis. The inadvertent creation of a rectourethral fistula during the procedure led to an urgent multidisciplinary approach involving surgery and postoperative management, including fecal and urine diversion and antibiotic therapy. The case highlights the critical importance of meticulous technique and comprehensive preoperative patient assessment in minimizing the risk of such iatrogenic complications. It further discusses the management strategies for rectourethral fistulas, ranging from conservative approaches to surgical interventions, and emphasizes the role of fecal diversion, urine diversion, and the potential of robotic surgery in enhancing outcomes for complex cases. The report concludes by reflecting on the intricate balance between routine medical procedures and the potential for severe complications, highlighting the need for heightened awareness and skill in the prevention and management of iatrogenic rectal perforation.